Devised Technology for Wireless Power Transmission - Muhanned Al-Rawi (Journal of Mechanical Engineering)
Wireless charging of gadgets is one of the new emerging technologies in the world at the moment. The most common method used at the moment is wireless power transfer by inductive coupling. Wireless power transfer is one of the simplest and inexpensive ways of charging as it eliminates the use of conventional copper cables and current carrying wires. In this paper, a methodology and principle of operation are devised for wireless power transfer through inductive coupling is described, and a feasible design is modeled accordingly. The inductive coupling technique is used since currently, it is the easiest method of wireless power transfer because of high efficiency and the possibility to transfer a large amount of energy. In this paper, results of experiments done to check wireless working are shown. Also, to further show its versatility and range of applications, the transferred power is used to charge a battery with the aid of additional circuitry. We also study the effect of placing hurdles between the transmitter and receiver so as to establish if such method could be an alternative in the medical industry for charging pace makers, etc. This research focuses on the study of wireless power transfer for the purpose of transferring energy at maximum efficiency within a small range or in the near field region.